American marten distributions over a 28 year period : relationships with landscape change in Sagehen Creek Experimental Forest, California, USA - Moriarty, Katie M.
The distribution of American martens (Martes americana) within Sagehen Creek Experimental Forest (SCEF), Tahoe National Forest, California has been periodically documented from 1980–1993. This area has been the location of nine marten surveys, each involving a systematic detection/nondetection survey on the same grid. These data are an unprecedented time series of information on the distribution of martens that can be related to habitat change in the study area. My four objectives were to (1) resurvey SCEF using similar methodology as in previous studies to assess the current marten distribution, (2) evaluate marten distribution over the last 28 years, (3) create maps to depict potential high reproductive habitat at the beginning (1978) and end (2007) of the series, and lastly, (4) examine marten occurence relative to changes in habitat and landscape metrics. Marten surveys were conducted in summer 2007, in winter 2007–2008, and in summer 2008. Habitat was characterized both in 1978 and 2007 by interpreting remotely sensed vegetation information from the California Wildlife Habitat Relationship (CWHR) system. I used FRAGSTATs to quantify landscape change. There was a dramatic decline in marten occurrence since they were first studied in this area. No martens were detected in either the summer of 2007 or summer 2008, but there were 10 detections in winter 2007–2008 limited to the southwestern portion of SCEF. Predicted habitat patch size, core area, and total amount of predicted habitat in the study area decreased. Distance between these patches increased. There was a relationship between these changes in landscape configuration and the reduction of marten detections; no martens were detected in the lower elevations where most previous management activity occurred. I have five recommendations to managers to make the landscape more amenable for martens: (1) strive to retain the remaining contiguous large patches of predicted marten reproductive habitat, (2) maintain corridors of dense, multilayered vegetation ...